PEDAGOGICAL OPPORTUNITIES OF TRAINING PSYCHOLOGICAL PERSONNEL FOR THE EDUCATIONAL SYSTEM (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
The article highlights the problems of psychological preparation of teachers and shows the changes in the socio-cultural context leading to changes in the educational environment. The article presents a psychological analysis of the nature of pedagogical activity and educates through the teaching process and shows the leading role of communication in pedagogical activity. This analysis creates a basis for determining the main areas of psychological knowledge necessary for a teacher education: general psychology, youth psychology and developmental psychology, social psychology, pedagogical psychology. The article examines the main concepts of psychological training, includes theoretical and practice-oriented teachers, and defines promising directions for the development of psychological training in pedagogical education